RNA interference of Argonaute‐1 delays ovarian development in the oriental fruit fly, Bactrocera dorsalis (Hendel). Issue 9 (11th May 2021) - Yang, Rui‐Lin; Zhang, Qiang; Fan, Jia‐Yao; Yue, Yong; Chen, Er‐Hu; Yuan, Guo‐Rui; Dou, Wei; Wang, Jin‐Jun
Abstract: BACKGROUND: With the development of rapid resistance, new modes of action for pesticides are needed for insect control, such as RNAi‐based biopesticides targeting essential genes. To explore the function of Argonaute‐1 ( Ago‐1 ) and potential miRNAs in ovarian development of Bactrocera dorsalis, an important agricultural pest, and to develop a novel control strategy for the pest, BdAgo‐1 was first identified in B. dorsalis . RESULTS: Spatiotemporal expression analysis indicated that BdAgo‐1 had a relatively high transcriptional level in the ovarian tissues of adult female B. dorsalis during the sexual maturation period. RNA interference (RNAi) experiment showed that BdAgo‐1 knockdown significantly decreased the expression levels of ovarian development‐related genes and delayed ovarian development. Although RNAi‐mediated silencing of Ago‐1 led to a reduced ovary surface area, a subsequent oviposition assay revealed that the influence was minimal over a longer time period. Small RNA libraries were constructed and sequenced from different ovarian developmental stages of B. dorsalis adults. Among 161 identified miRNAs, 84 miRNAs were differentially expressed during the three developmental stages of the B. dorsalis ovary. BdAgo‐1 silencing caused significant down‐regulation of seven differentially expressed miRNAs (DEMs) showing relatively high expression levels (>1000 TPM (Transcripts per kilobase of exon model per million mapped reads)). The expression patterns of these seven core DEMs and their putative target genes were analyzed in the ovaries of B. dorsalis . CONCLUSION: The results indicate that Ago‐1 and Ago‐1 ‐dependent miRNAs are indispensable for normal ovarian development in B. dorsalis and help identify miRNA targets useful for control of this pest. Abstract : The function of Ago‐1 in the regulation of ovarian development in Bactrocera dorsalis was systematically investigated. BdAgo‐1 knockdown significantly decreased the expression levels of ovarian development‐related genes and thus delayed ovary development. Although RNAi‐mediated silencing of Ago‐1 led to a reduced ovary surface area, a subsequent oviposition assay revealed that the influence was minimal over a longer time period. Subsequent deep sequencing of small RNAs has allowed the identification of 84 differentially expressed miRNAs (DEMs) at three ovarian development stages, indicating that these DEMs may play important regulatory roles in the progress of ovary development. BdAgo‐1 silencing caused significant down‐regulation of the seven core DEMs. For these seven highly expressed DEMs, 15 putative target genes were predicted and their expression patterns were analyzed in different ovary stages. © 2021 Society of Chemical Industry.